Response of Sweet Corn Plants (Zea mays saccharata L.) Affected the Aplication of Biological Liquid Compound Fertilizer and Synthetic Fertilizer N, P and K - Rahayu, Arifah; Rochman, Nur; Lestari, Nurfitri Dwi; Agustina, Karlin (JURNAL AGRONIDA, 2019)
This study was aimed at assessing the response of sweetcorn plant on various dosages of biofertilizer and synthetic (N, P and K) fertilizer. The study was done in May to September 2014 at the Agrotechnology Trial Farm of Djuanda University. A factorial completely randomized design was used. The first and second factor were biofertilizer and synthetic fertilizer dosage (0%, 50 %, 100% and 150% R/Recommendation). Results showed that adding biofertilizer and synthetic fertilizer until 100% R increased leaf area, length and weight of ear, root and biomass weight and TSS (total soluble solids) content. At various level of biofertilizer, increasing synthetic fertilizer dosages until 100% R could improve plant height, leaves and root number, stem girth, ear length and accelerate growing of staminate and pistillate. Meanwhile at various degree of synthetic fertilizer dosage, raising bofertilizer dosage until 150% R tend to higher plant height, and until 100% R caused stem girth and root length greater, but delayed staminate and pistillate growth. Application of biofertlizer and synthetic fertilizer tend to increasing pH and cation exchange capacity of growth medium. Keywords: weight of ear, pH, cation enxchange capacity